A cobertura jornalística da Revista Veja sobre a crise política de 1992 - Juchem, Vinícius Viana (Universidade do Vale do Rio dos Sinos, 2013)
The political crisis which resulted in the renouncement of Fernando Collor de Mello from the republic presidency in 1992 is a historical happening that caused a considerable impact in the social and political environments. The impeachment process was never seen until then, and the popupaltion manifestations that went out on the streets to ask for removal of Collor was a mark in time. Since Veja's interview in which Pedro Collor, the president's brother, denounced him as a benefiter of a large corruption scheme that was architected by the entrepeneur Paulo César Farias, brazilian press, with emphasis in the mentioned megazine, it developed an important role when publishing denounciations of corruption or even investigating them. Facing the relevance of Veja throughout covering the political crisis, it was selected as the main research source. For analysis, two sections of the periodic were chosen – "Carta ao leitor" (letter to the reader) and the one signed by Jô Soares -- to answer the following question: how has Veja speech reverbereted in the political crisis and in what measure the referred sections of the periodical approached it some different way. The analysis starts by Pedro Collor's interview, in may of 1992, and encloses until the last edition of the same year, when the political crisis was the main subject in both analysed sections. Others, such as political reports, were used as complementary to contextualize the happenings. The purpose is to contribute for the conjunct of historiographical studies about the way information vehicles act, particularly about political deep crisis. It is expected that this monography contributes for some more acute comprehension of a complex chapter of the recent brazilian political history.
Keywords: Crise política; Revista Veja; Fernando Collor de Mello; Political crisis; Veja magazine; ACCNPQ::Ciências Humanas::História